[Book Review] Ungrading: Why Rating Students Undermines Learning (and What to do Instead), edited by Susan D. Blum - Green, Corinne A.; West, Conor; Delahunty, Janine (Teaching and Learning Inquiry, 2022)
Book review of Ungrading: Why Rating Students Undermines Learning (and What to do Instead), edited by Susan D. Blum.